PERBEDAAN MOTIVASI BERPRESTASI MAHASISWA SEMESTER VII-A JALUR SELEKSI PBUD DENGAN MAHASISWA SEMESTER VIIB JALUR SELEKSI LOKAL PADA PRODI PG PAUD FKIP UNIVERSITAS RIAU - Indarto, Wusono; Achmad, Said Suhil (SOROT, 2013)
This research was intended to find out the disparity ofmotivation of achievement of the 7th term student selected outthrough PBUD selection and ones picked out through local selectionat the study program of PG PAUD in FKIP UR. This paper was acomparative research that it compared the indicator and variable toagroup of respondents. The data was collected by using aninstrument in form of serveyor, in where the serveyor was developedfrom a variable of motivation with three indicators. Indicator I: therisk taker consisted of 12 discriptors; Indicator II: ones who neededfeedback consisted of 8 discriptors; and Indicator III: ones whoconsidered succes consisted of 8 discriptors. The number of alldiscriptors was 28 units. After being tested for the validity, 4 of themwere invalid. The population of this research was 94 student who 42of them were the students from PBUD selection and the other 52were from the local selection. The sample of the research was 64students, 30 of them were from PBUD selection and the other werefrom the local selection.Based on the data collected, the score of motivation of achievementof the PBUD studends was 79.833 and percentage was 83.16%. Thenumber of percentage was “very high” after being matched withcriterion. While the score of local selected students was 76.4112 oethe number in percent was 79.63% which was considered in the levelof high. While in the hypothesis of search testing with computercalculation, it was showed that there was a disparity of themotivation of the students selected through PBUD selection to theones picked out through local selection at the study program of PGPAUD in FKIP UR. Based on the calculation of thitung, the result was3.698327 higher than ttabel which was only <3.698327> 2.617 in thelevel of significance 0.01. Thus, Ho was rejected, which meant thatthere was a disparity of motivation on achievement of the 7th termstudents of PBUD selection and the students of local selection.